As‐needed anti‐inflammatory reliever therapy for asthma management: evidence and practical considerations. Issue 7 (20th December 2020) - Bianco, Andrea; Contoli, Marco; Di Marco, Fabiano; Saverio Mennini, Francesco; Papi, Alberto; ,
Abstract: Asthma is a chronic respiratory disease in which airway inflammation is a key feature, even in the milder expressions of the disease. The conventional pharmacological approach to mild asthma has long relied on reliever therapy with as‐needed short‐acting beta‐agonists (SABAs), while anti‐inflammatory maintenance with inhaled corticosteroids (ICSs) has been reserved for patients with more persistent asthma. Poor adherence to maintenance treatment is an important issue in asthma management, and can partly explain suboptimal symptom control. Over‐reliance on SABA bronchodilators for rapid symptom relief is common in real life and potentially leads to an increased risk of asthma morbidity and mortality. Combined anti‐inflammatory and reliever medications in a single inhaler have the potential to overcome these limitations. Recent studies in patients with mild asthma have shown that anti‐inflammatory reliever therapy with budesonide‐formoterol, given on an as‐needed basis, is superior to SABA in ensuring asthma control and non‐inferior to budesonide maintenance therapy in preventing exacerbations. To address the implications of these important findings for the management of patients with asthma, Italian specialists convened at a series of meetings held during the second half of 2018 across Italy. This article presents their position on these topics and includes a review of the evidence supporting the use of anti‐inflammatory reliever therapy in mild asthma and the implementation of this novel approach in clinical practice.